Integrated DFIG–SCIG‐based wind energy conversion system equipped with improved power generation capability. Issue 15 (2nd October 2017) - Parida, Adikanda; Chatterjee, Debashis
Abstract : The grid‐connected doubly fed induction generator (DFIG)‐based wind energy conversion systems (WECSs) draws special attention as a potential renewable energy source in recent past. In this study, an integrated WECS equipped with improved active power generation capability has been proposed. The said generation scheme will harvest an enhanced power in the supersynchronous operating region which otherwise bypassed through pitch control process. The proposed hybrid generation scheme can be operated virtually much beyond the existing specified slip limit with the help of an integrated squirrel cage induction generator (SCIG). A solar photovoltaic generation system has also been augmented with the proposed scheme to utilise the facility available for WECS to further enhance the active power generation over subsynchronous operating region. The proposed scheme has been validated through proper simulations and experiments on a practical DFIG of 7.5 kW and an SCIG of 2.5 kW capacity which produced satisfactory results.